An Optimal Corrective Tax for Thai Shrimp Farming - Tipparat Pongthanapanich (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2005)
If Thai shrimp farming were taxed, how much should it be? is the key re-search question of this paper. The dynamic-constraint optimization model in-corporating accumulated nutrient load from farm discharges is applied in the analysis. The model implies some tax has to be imposed on stock externality that is equal to increasing shadow cost of nutrient stock before damage occurs. However, the simulation results show very small shadow costs at the beginning of the paths and indicate that nutrient load in Andaman has a negligible effect on the sea but significant on the Gulf of Thailand. A socially efficient level of production for Thailand would be around 70-80% of private optimal produc-tion. The tax regime ensures a higher net gain from trade than at private opti-mum but it is ambiguous in term of net social welfare.
Keywords: 330; Green tax; stock externality; shrimp farming; Gulf of Thailand; Andaman Sea; Krebstiere; Aquakultur; Ökosteuer; Optimale Besteuerung; Thailand; Externer Effekt